2006
DOI: 10.1074/jbc.m506303200
|View full text |Cite
|
Sign up to set email alerts
|

Binding of PAI-1 to Endothelial Cells Stimulated by Thymosin β4 and Modulation of Their Fibrinolytic Potential

Abstract: Our previous studies showed that thymosin ␤4 (T␤4) induced the synthesis of plasminogen activator inhibitor-1 (PAI-1) in cultured human umbilical vein endothelial cells (HUVECs) via the AP-1 dependent mechanism and its enhanced secretion. In this work we provide evidence that the released PAI-1 is accumulated on the surface of HUVECs, exclusively in its active form, in a complex with ␣1-acid glycoprotein (AGP) that is also up-regulated and released from the cells. This mechanism is supported by several lines o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 26 publications
1
17
0
Order By: Relevance
“…Additionally, we cannot exclude the possibility that a chronic increase in Orm expression in circulation might play unwanted roles in affecting metabolic complications in obese subjects. Indeed, it has been recently reported that ORM interacts with PAI-1 to recruit prothrombotic activity to atherosclerotic lesions (44). Thus, further studies are required to explain the persistence of elevated inflammatory responses despite the induced expression of Orm in obese mice and to address the role of increased levels of Orm expression in obesity-related metabolic complications and cardiovascular diseases, emphasizing the importance of analyzing conditional Orm gene knock-out mice.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we cannot exclude the possibility that a chronic increase in Orm expression in circulation might play unwanted roles in affecting metabolic complications in obese subjects. Indeed, it has been recently reported that ORM interacts with PAI-1 to recruit prothrombotic activity to atherosclerotic lesions (44). Thus, further studies are required to explain the persistence of elevated inflammatory responses despite the induced expression of Orm in obese mice and to address the role of increased levels of Orm expression in obesity-related metabolic complications and cardiovascular diseases, emphasizing the importance of analyzing conditional Orm gene knock-out mice.…”
Section: Discussionmentioning
confidence: 99%
“…Proteins released from the resin were separated by electrophoresis by 7% SDS-PAGE, electrotransfered onto nitrocellulose membranes, and immunodetected by HA tag mouse monoclonal antibody. Immunoprecipitation of the Ku80⅐T␤4 complex from endothelial cell extracts was performed as described previously (26).…”
Section: Construction Of Ku80 Deletion Mutants and T␤4 In The Pcmvmentioning
confidence: 99%
“…Thus, T␤4 externally added to endothelial cells: (a) induces expression and release of plasminogen activator inhibitor type 1 (PAI-1) by the mechanism involving activation of the mitogen-activated protein kinase cascade leading to enhanced c-Fos/c-Jun binding to the AP-1-like element present in the PAI-1 promoter (25,26); (b) binds to PINCH and integrinlinked kinase, resulting in activation of the survival kinase Akt, and thus promotes myocardial and endothelial cell migration in the embryonic heart (27) and (c) promotes skin and corneal wound healing through its effects on cell migration, angiogenesis, and possibly cell survival (4,6,11).…”
mentioning
confidence: 99%
“…T␤4 could also induce NK cell activation via direct stimulation of the signal machinery or the phosphorylation of transcription factors. It is well known that T␤4 stimulates integrin-linked kinase (ILK) and AKT/Protein Kinase B in cardiomyocyte survival and ERK phosphorylation in paclitaxelinduced cell death and activates plasminogen activator inhibitor-1 (PAI-1) and then induces JAK/STAT cascade (Srivastava et al 2007;Boncela et al 2006;Oh et al 2006). Furthermore, IFN-␥ induction is mediated by the JAK/STAT pathway, which is also involved in actin polymerization (Jacobson et al 1995).…”
Section: Discussionmentioning
confidence: 99%